1993
DOI: 10.1037/0735-7044.107.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced changes in plasma proteins, angiotensin II, and salt appetite in rats.

Abstract: Sodium depletion in rats elicits a sodium appetite that results from a cerebral action of angiotensin II (ANG II) and aldosterone. Alcohol also activates the renin-angiotensin system, but the mechanism is poorly understood and not related to sodium excretion. In this study, 2.5 g/kg ip ethanol produced a 20% decline in plasma volume and plasma protein concentration in 1-2 hr and elicited salt appetite beginning in 3-4 hr. Blockade of ANG II synthesis in the brain and periphery with the angiotensin-converting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Chronic ethanol intake has been reported to decrease APA and APN activities in mouse cerebellum [22], supporting previous findings where the increased Ang II levels were found after ethanol intake [6, 23]. Moreover, time-dependent reduction of lysosomal APN activity in mouse kidney was demonstrated 14 days after 10 and 20% ethanol administration [24].…”
Section: Discussionsupporting
confidence: 76%
“…Chronic ethanol intake has been reported to decrease APA and APN activities in mouse cerebellum [22], supporting previous findings where the increased Ang II levels were found after ethanol intake [6, 23]. Moreover, time-dependent reduction of lysosomal APN activity in mouse kidney was demonstrated 14 days after 10 and 20% ethanol administration [24].…”
Section: Discussionsupporting
confidence: 76%
“…Ethanol accumulation might be considered a key pathway. The possible mechanisms by which ethanol increases blood pressure include: (a) a direct effect on the central nervous system, by interfering with central inhibitory pathways, which control the vasomotor center or increasing sympathetic activity, 25 (b) activation of the rennin–angiotensin system by ethanol, 26 (c) aortic endothelial oxidative injury and downregulation of the nitric oxide generating system, 27 and (d) magnesium deficiency. 28 However, the actual effect of ethanol on blood pressure is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a recent study reported that infusion of angiotensin II (Ang II) produced an upregulation of gp91phox expression in adipose tissue, aorta and heart (Hattori et al, 2005). Alcohol consumption robustly activates the renin-angiotensin system and increases plasma concentration of Ang II (Fitts and Hoon, 1993;Wright et al, 1986). Thus, upregualted NAD(P)H oxidase during alcohol consumption may be related to increased Ang II.…”
Section: Discussionmentioning
confidence: 97%